The application of mental fatigue research to elite team sport performance: New perspectives - Russel, S.; Jenkins, D.; Smith, M.; Halson, S.; Kelly, V. (Journal of Science and Medicine in Sport, 2019)
Objectives: Mental fatigue resulting from prolonged periods of demanding cognitive activity, has been found to impair endurance exercise performance and performance in some sport-specific tasks. The application of such research to the elite sporting environment however is limited. Design & Methods: This article reviews the literature relevant to mental fatigue and team sporting performance with aim to provide perspectives on the transferability and significance of currently available evidence to the applied elite sporting context. Results: Inconsistent findings in the limited available literature can be attributed to large variations in the participants involved, the nature of the cognitively demanding tasks used to induce mental fatigue and the tests used to assess performance outcomes. Few studies have used trained athletes in combination with performance tests that accurately represent the physiological and technical demands experienced by athletes in competition. While there is growing interest in the acute influence of mental fatigue on exercise performance, a potential cumulative effect of mental fatigue on performance over, for example, a competitive season is an area yet to be investigated. Conclusions: If it is accepted that mental fatigue impairs the performance of some athletes, then improving the ecological validity of research in the area of mental fatigue and sport will significantly advance our understanding of how to better monitor and manage mental fatigue. At the elite level of competition, where outcomes are determined by very small margins of difference, reducing the impact of mental fatigue on performance has potential to be significant.